2005
DOI: 10.1038/sj.jcbfm.9600008
|View full text |Cite
|
Sign up to set email alerts
|

Development of Posttraumatic Hyperthermia after Traumatic Brain Injury in Rats is Associated with Increased Periventricular Inflammation

Abstract: Posttraumatic hyperthermia (PTH) is a noninfectious elevation in body temperature that negatively influences outcome after traumatic brain injury (TBI). We sought to (1) characterize a clinically relevant model and (2) investigate potential cellular mechanisms of PTH. In study I, body temperature patterns were analyzed for 1 week in male rats after severe lateral fluid percussion (FP) brain injury (n ¼ 75) or sham injury (n ¼ 17). After injury, 27% of surviving animals experienced PTH, while 69% experienced ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 70 publications
1
27
0
Order By: Relevance
“…Available literature on experimental models of TBI indicate injury induction via fluid percussion or controlled cortical impact, where skull is invariably removed and direct trauma to the brain tissue, produces moderate to severe TBI (Morales et al, 2005) resulting in focal lesions, blood-brain barrier (BBB) disturbances, edema formation, and morphologically evident brain damage (Carbonell and Grady, 1999;Graham et al, 2000;Thompson et al, 2005). Since craniotomy is indispensable in these models, mTBI models developed through these methods may lead to ignoring some pathophysiological alterations speculated in mTBI.…”
Section: Introductionmentioning
confidence: 98%
“…Available literature on experimental models of TBI indicate injury induction via fluid percussion or controlled cortical impact, where skull is invariably removed and direct trauma to the brain tissue, produces moderate to severe TBI (Morales et al, 2005) resulting in focal lesions, blood-brain barrier (BBB) disturbances, edema formation, and morphologically evident brain damage (Carbonell and Grady, 1999;Graham et al, 2000;Thompson et al, 2005). Since craniotomy is indispensable in these models, mTBI models developed through these methods may lead to ignoring some pathophysiological alterations speculated in mTBI.…”
Section: Introductionmentioning
confidence: 98%
“…24 post-trauma hours. In another experimental study by Thomson et al [10], brain damage resulted in CF in 27% of animals while acute hypothermia was observed in 69% of subjects. The development of CF was associated with the inflammatory changes within the hypothalamus.…”
Section: Central Fever In Various Clinical Conditions Head Injurymentioning
confidence: 99%
“…In humans and laboratory animals, TBI can induce the accumulation of alpha-synuclein (Knoblach and Faden, 1998;Thompson et al, 2005a;Uryu et al, 2003), and a neuroinflammatory response (Csuka et al, 1999;Holmin and Hojeberg, 2004;Holmin et al, 1995), similar to what is observed in PD (Braak et al, 2002(Braak et al, ,2006Gerhard et al, 2006;Imamura et al, 2003;McGeer et al, 1988). Lateral fluid percussion (LFP) injury, a model of experimental TBI (McIntosh et al, 1989;Thompson et al, 2005a), induces the presence of silver-stained and lipofuschin-containing neurons in the substantia nigra (SN) of adult rats (Hicks et al, 1996). However, the phenotype of the injured neurons was not determined, and no stereological evaluation of the number of nigrostriatal neurons was performed (Hicks et al, 1996).…”
mentioning
confidence: 99%